Analisis Risiko dan Pengendalian K3 di Area Workshop pada Garasi Angkutan Luar PT. XYZ Menggunakan Metode Job Safety Analysis (JSA) - Inas Putri Salsabillah; Hidayat Hidayat; Akhmad Wasiur Rizqi (Jurnal Optimalisasi, 2023)
PT. XYZ is a company engaged in logistics facilities for industry which provides services for commodity management, commodity transportation, commodity distribution, industrial land preparation, workshops and various other service needs. Organizational structure at PT head office. XYZ is divided into 16 fields starting from K3, HR, internal transportation, external transportation and so on. The external transportation sector is a field that is tasked with regulating transportation operations such as dump trucks to transport fertilizers outside the PT area. XYZ and outside the city, and in the external transport garage there are two activities, namely office activities and dump truck repair activities such as welding work and other repair activities which have a risk of work accidents due to this work, as well as potential dangers, for example exposure to dust and smoke, exposure to welding rays, and the risk of fire is also prone to occur. JSA (Job Safety Analysis) is a method used as a consideration in identifying hazards in the work environment and determining controls that are deemed appropriate in an effort to control the occurrence of work accidents. The aim of this research is to find out how to analyze potential hazards that arise and efforts to control them. This research is devoted to analyzing risks in the welding section in the workshop area of PT's external transportation garage of XYZ. From the results of the risk assessment in the dump truck welding section, it can be seen that the types of hazards have a high classification level, namely: Exposure to welding light 15, exposure to dust, smoke and gas 15, electric shock 15, noise 15, and those with a medium classification level. /Medium, namely: Fire 10, exposure to sparks 12, and those with a low/Low classification level, namely: exposure to a hot plate 4.